EVALUASI FAKTOR RISIKO KEJANG DEMAM BERULANG DI RUMAH SAKIT UMUM HAJI MEDAN - HIRDA HARFIZI; NUR CAHAYA (LP2MTBM MAKARIOZ, 2022)
Recurrent febrile seizures are seizures 2 or more times in 1 day, and between 2 seizures the child is conscious. Recurrent febrile seizures occurred in 16% of children who had febrile seizures. Knowledge about febrile seizures and risk factors that cause recurrent febrile seizures is needed in hospitalized children. Methods: The research method is retrospective with a cross-sectional study design. The research subjects were 49 cases of recurrent febrile seizures diagnosed and registered in the medical records of RSU Haji Medan for the period September 2017-September 2019 and met the inclusion and exclusion criteria. The sampling technique uses the total sampling method. The resultt ofthis research There was a relationship between the type of febrile seizures and recurrent febrile seizures, whereas the family history of febrile seizures, family history of epilepsy, age <12 months, gender, and low temperature were not associated with recurrence of febrile seizures